Nor-isoprenoids profile during port wine ageing—influence of some technological parameters - Ferreira, António César Silva (2010)
Nor-isoprenoid compounds, such as β-damascenone, β-ionone, 2,2,6-trimethylcyclohexanone (TCH), 1,1,6-trimethyl-1,2-dihydronaphthalene (TDN) and vitispirane were determined in 14 young port wines and 45 old port wines. As between the two groups of wines levels of these compounds are quite different, an experimental protocol was performed in order to determine which technological parameter (dissolved O2, free SO2 levels, pH and time/temperature) was related with the formation/consumption of these molecules. The five nor-isoprenoids were equally affected by the selected parameters and a similar profile with time was observed. The synergistic effects of increasing temperature and lowering pH had the largest impact. For samples treated with high oxygen regimes (saturation), the levels of all considered nor-isoprenoids decreased after a certain concentration of oxygen consumed (e.g. 10 mg l−1). Nevertheless, during barrel port wine ageing, corresponding to the 45 wines, two different behaviours can be observed: TDN, vitispirane and TCH increase significantly whilst a decrease of levels of β-ionone and β-damascenone with port barrel ageing was observed. It was also calculated that “over 40 year” old port wines have, respectively, 15, 5 and 3 times higher levels of TDN, vitispirane and TCH than the young ports. For these three compounds the respective rates of formation are higher than those of degradation, which suggests a higher number or higher concentration of precursors than those involved for the megastigame C13 nor-isoprenoids β-damascenone and β-ionone.